2022
DOI: 10.3390/biomedicines10112697
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Complete Blood Count (CBC) to Assess Cardiovascular and Metabolic Diseases in Clinical Settings: A Comprehensive Literature Review

Abstract: Complete blood count (CBC) is one of the most common blood tests requested by clinicians and evaluates the total numbers and characteristics of cell components in the blood. Recently, many investigations have suggested that the risk of cancer, cardiovascular disease (CVD), arteriosclerosis, type 2 diabetes (T2DM), and metabolic syndrome can be predicted using CBC components. This review introduces that white blood cell (WBC), neutrophil-to-lymphocyte ratio (NLR), hemoglobin (Hb), mean corpuscular volume (MCV),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 80 publications
3
33
0
Order By: Relevance
“…33 Particularly, emerging evidence suggests that PLR has also been proposed as a marker for kidney diseases. 34 In this study, we found that the patients with poor treatment effects, whose serum ALB levels were less than 30g/L at 6 months or who did not reach CR at the end of the follow-up, had numerically higher PLR. Especially for patients with CR or not, the difference was near to statistic significant.…”
Section: Discussionmentioning
confidence: 54%
“…33 Particularly, emerging evidence suggests that PLR has also been proposed as a marker for kidney diseases. 34 In this study, we found that the patients with poor treatment effects, whose serum ALB levels were less than 30g/L at 6 months or who did not reach CR at the end of the follow-up, had numerically higher PLR. Especially for patients with CR or not, the difference was near to statistic significant.…”
Section: Discussionmentioning
confidence: 54%
“…Some studies showed that PLR could be potentially valuable in the accurate evaluation of in ammatory activity [14] , and others demonstrated that high PLR was associated with venous thrombosis [25] . Particularly, emerging evidence suggests that PLR has also been proposed as a marker for kidney diseases [15] . In this study, we found that the patients with poor treatment effects, whose serum ALB levels were less than 30g/L at 6 months or who didn't reach CR at the end of the follow-up, had numerically higher PLR.…”
Section: Discussionmentioning
confidence: 99%
“…These monocytes differentiate into macrophages and create an in ammatory state [15] . Some kidney macrophages have been demonstrated to be able to promote kidney brosis [28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These leukocyte-derived indices integrate information from the innate and adaptive immunity to avoid relying on the absolute value of a single leukocyte subtype caused by infection or dehydration. Evidence from observational studies has demonstrated a significant association between these inflammation indices and the incidence and severity of many cardiovascular diseases, such as heart failure, myocardial infarction, and hypertension [ 10 ]. However, to date, no studies have investigated the predictive value of inflammation indices for LAT in VAF patients.…”
Section: Introductionmentioning
confidence: 99%